Immunization with recombinant Salmonella expressing SspH2-EscI protects mice against wild type Salmonella infection - Hu, Maozhi (BMC Vet Res, 2018)
BACKGROUND: Enhancing caspase-1 activation in macrophages is helpful for the clearance of intracellular bacteria in mice. Our previous studies have shown that EscI, an inner rod protein of type III system in E. coli can enhance caspase-1 activation. The purpose of this study was to further analyze the prospect of EscI in the vaccine design. RESULTS: A recombinant Salmonella expressing SspH2-EscI fusion protein using the promotor of Salmonella effector SspH2, X4550(pYA3334-P-SspH2-EscI), was constructed. A control recombinant Salmonella expressing SspH2 only X4550(pYA3334-P-SspH2) was also constructed. In the early stage of in vitro infection of mouse peritoneal macrophages, X4550(pYA3334-P-SspH2-EscI) could significantly (P < 0.05) enhance intracellular caspase-1 activation and pyroptotic cell death of macrophages, when compared with X4550(pYA3334-P-SspH2). Except for the intracellular pH value, the levels of reactive oxygen species, intracellular concentration of calcium ions, nitric oxide and mitochondrial membrane potential in macrophages were not significantly different between the cells infected with X4550(pYA3334-P-SspH2-EscI) and those infected with X4550(pYA3334-P-SspH2). Besides, only lower inflammatory cytokines secretion was induced by X4550(pYA3334-P-SspH2-EscI) than X4550(pYA3334-P-SspH2). After intravenous immunization of mice (1 × 10(6) cfu/mouse), the colonization of X4550(pYA3334-P-SspH2-EscI) in mice was significantly limited at one week post immunization (wpi), when compared with X4550(pYA3334-P-SspH2) (P < 0.05). The population of activated CD8(+)T lymphocytes in mouse spleens induced by X4550(pYA3334-P-SspH2-EscI) was lower than that induced by X4550(pYA3334-P-SspH2) at 2–3 wpi, and the ratio of CD4(+)T cells to CD8(+)T cells decreased. The blood coagulation assay indicated that no significant difference was found between X4550(pYA3334-P-SspH2-EscI) and uninfected control, while X4550(pYA3334-P-SspH2) could induce the quick coagulation. Notably, immunization of X4550(pYA3334-P-SspH2-EscI) could limit the colonization of challenged Salmonella strains in the early stage of infection and provide more effective protection. CONCLUSION: The activation of caspase-1 in macrophages by EscI can be used in the design of live attenuated Salmonella vaccine candidate.